An experimental analysis of evacuees' walking speeds under different rolling conditions of a ship. (1st August 2021) - Wang, Xinjian; Liu, Zhengjiang; Loughney, Sean; Yang, Zaili; Wang, Yanfu; Wang, Jin
Abstract: During the emergency evacuation on passenger vessels, an individual's walking speed will be affected by the ship's rolling motions. It is necessary and beneficial to evaluate the effect of such motions on individuals' walking speeds in order to facilitate the evacuation and reduce the consequence of a maritime accident. In this study, we collected primary data from a series of walking experiments on-board a real ship to quantitatively evaluate the effect of different ship roll angular magnitudes on an individual's walking speed in two scenarios of flat terrains and staircases, respectively. It was found that on flat terrains, the ship's rolling motion results in the reduction of an individual's walking speed at a rate of 7%–16%. On a staircase, an individual's speed of walking up the staircases was reduced by approximately 5% due to the ship's rolling motion. The findings will contribute to the development of optimal evacuation routes on passenger ships. The used method can also be tailored to model the effect of the other dynamic environments on walking speeds at sea ( e.g ., on offshore platforms) and onshore ( e.g ., during earthquakes) to improve evacuation efficiency for disaster prevention. Highlights: The primary data from a series of walking experiments onboard a real ship was collected. The effect of different ship rolling angles on an individual's walking speed was evaluated. An individual's walking speed was reduced at a rate of 7%–16% on flat terrains. An individual's speed of walking up stairs was reduced by 5% on a staircase. The differences of individuals' walking speeds between male and female were observed and analysed.